Seafloor sealing, doming, and collapse associated with gas seeps and authigenic carbonate structures at Venere mud volcano, Central Mediterranean. (July 2018) - Loher, Markus; Marcon, Yann; Pape, Thomas; Römer, Miriam; Wintersteller, Paul; dos Santos Ferreira, Christian; Praeg, Daniel; Torres, Marta; Sahling, Heiko; Bohrmann, Gerhard
Abstract: Methane release from the seafloor is commonly associated with chemosynthesis-based cold seep ecosystems that facilitate the precipitation of authigenic carbonates. It has been proposed that carbonate growth results in self-sealing, but little is known regarding the evolution of cold seep structures in relation to fluid migration pathways. This study investigates structures resulting from gas seepage along ring faults peripheral to Venere mud volcano (1600 m water depth), based on multibeam bathymetry and seafloor backscatter data collected by an autonomous underwater vehicle, together with photomosaics, video observations, and samples obtained by a remotely operated vehicle. Sites of focused fluid flow are identified by gas bubble streams rising from the seafloor while anaerobic oxidation of methane (AOM) over wider areas is indicated by the occurrence of chemosynthesis-based organisms (microbial mats, vesicomyid clams, vestimentiferan tube worms). At some sites, flakes of gas hydrate were observed in the water column during sampling. A range of carbonate structures exists at these sites: 1) flat and extensive pavements; 2) mounds with disseminated nodules or centimeter-thick crusts; 3) fractured mounds with exposed, decimeter-thick crusts; and 4) seafloor depressions lined by decimeter-thick crusts. The mineralogy and stable carbon isotopic compositions of the carbonates are consistent with anaerobic oxidation of methane from thermogenic sources, and possible near-seabed influence of gas hydrate formation and dissolution. The seafloor expressions of seepage are inferred to be controlled by the interaction of fluid flow due to carbonate precipitation and gas hydrate formation. A conceptual model for mound development is proposed in the context of the known timescales of seep-colonization and rates of carbonate precipitation: (A) the onset of hydrocarbon-rich fluid seepage through hemipelagic sediments leads to (B) the establishment of microbial mats on flat seafloor over decadal timescales and is followed by (C) the growth of pavements cemented by carbonates that seal the seafloor; over longer timescales (centuries to millennia), carbonate growth and subsurface gas hydrate formation/dissolution lead to (D) upward doming and fracturing of carbonate mounds, re-sealing and stacking of carbonates and in some cases to (E) their collapse to form seafloor depressions. Gas migration through fractures in the carbonates allows re-sealing and fuels AOM to provide habitats for chemosynthesis-based fauna. This evolutionary scenario is argued to be broadly applicable to the development of ruptured mounds and collapse features described at other seepage sites in the Mediterranean Sea and elsewhere. Highlights: Photomosaic- and multibeam-based mapping of cold seeps at Venere mud volcano. Methane-rich fluids sustain oasis-type ecosystems and carbonate precipitation. Carbonate self-sealing, rupturing, and collapse influence morphology of the seeps. Fluid migration, accumulation, and release govern cold seep evolution.